Transport of adenine, hypoxanthine and uracil into Escherichia coli. - Burton, K (1977)
Uptake of adenine, hypoxanthine and uracil by an uncA strain of Escherichia coli is inhibited by uncouplers or when phosphate in the medium is replaced by less than 1 mM-arsenate, indicating a need for both a protonmotive force and phosphorylated metabolites. The rate of uptake of adenine or hypoxanthine was not markedly affected by a genetic deficiency of purine nucleoside phosphorylase. In two mutants with undetected adenine phosphoribosyltransferase, the rate of adenine uptake was about 30% of that in their parent strain, and evidence was obtained to confirm that adenine had then been utilized via purine nucleoside phosphorylase. In a strain deficient in both enzymes adenine uptake was about 1% of that shown by wild-type strains. Uptake of hypoxanthine was similarly limited in a strain lacking purine nucleoside phosphorylase, hypoxanthine phosphoribosyltransferase and guanine phosphoribosyltransferase. Deficiency of uracil phosphoribosyltransferase severely limits uracil uptake, but the defect can be circumvented by addition of inosine, which presumably provides ribose 1-phosphate for reversal of uridine phosphorylase. The results indicate that there are porter systems for adenine, hypoxanthine and uracil dependent on a protonmotive force and facilitated by intracellular metabolism of the free bases.